Hippocrates of Kos – ophthalmologic aspects in the work of father of medicine - Bieganowski, Lech (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The article presents the life and work of an outstanding physician of ancient Greece - Hippocrates of Kos (460 - 370 B.C.). He is known as the father of medicine, because of his achievements in laying the foundations of medical knowledge and ethical aspects of medical profession, which is outlined in the article. A particular attention is given to ophthalmologic aspects of his work found in various Corpus Hippocraticum treaties. His views on the anatomy of the eye are presented as well. Reconstruction of the eye according to Hippocrates and Aristotle is included in the article. It also presents the International Foundation of Hippocrates of Kos.